Effect of electrical field on the stability of hydration products of cement paste in different liquid media. (12th December 2022) - Fang, Zheng; Wang, Chong; Hu, Haoyue; Zhou, Shuai; Luo, Yaoling
Highlights: The effects of the electrical field and different liquid media on hydration products were studied. The portlandite had been proved to be affected by the electrical field. The pure water affected the stability of CSH gel under the electrical field. The fractal model was used to analyze the pore structure and morphology of hydration products. Abstract: Electrical fields accelerate the sulfate attack, which induces detrimental effects on the durability of cement-based materials. However, the role of the electrical field and aggressive liquid media in the degradation process is still unclear. Investigation of the role of the electrical field and aggressive liquid media during the degradation allows a better understanding of the mechanism of accelerated technique. Four different liquid media were used in this work to study the effect of the electrical field and liquid media in terms of the stability of hydration products. The evolution of hydration products was experimentally identified using multiple techniques, including X-ray diffraction (XRD), thermogravimetric analysis (TG), transmission electron microscopy (TEM), nitrogen adsorption/desorption (NAD), pH and CaO content measurements. The results indicated that the CSH structure was stable under the electrical field and saturated Ca(OH)2 solution. The calcium loss under the electrical field was more likely to leach out from portlandite even though the mixed Ca(OH)2 -Na2 SO4 solution was present. A severe degradation occurred under the electrical field and low-pH liquid media (pure water, Na2 SO4 -MgSO4 solutions). The Ca/Si ratio significantly decreased from 1.34 to 0.82 under the coupling effect of the electrical field and Na2 SO4 -MgSO4 solutions. Based on the fractal dimension results derived from NAD and TEM, the variations of pore structure and CSH gel morphology were quantitatively characterized. The coupled electrical field and low-pH liquid media dramatically altered the microstructure of hydration products, resulting in coarser pore networks and a shift to the disordered CSH gel.